2019
DOI: 10.1002/ijgo.12766
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of reported outcomes and outcome measures in randomized controlled trials on apical prolapse surgery

Abstract: Background Evidence on efficacy and safety of pelvic organ prolapse interventions is variable, and methodological flaws preclude meaningful synthesis of primary research data. Objective To evaluate variations in reported outcomes and outcome measures in randomized controlled trials (RCTs) on apical prolapse surgical interventions. Search strategy We searched Cochrane, EMBASE, MEDLINE, and Scopus for English‐language articles published from inception to September 30, 2017, using the terms “management”, “repair”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…This systematic review aimed to evaluate the selection and reporting of outcomes and the use of outcome measures in RCTs evaluating surgical treatments for posterior vaginal prolapse. We demonstrated a wide variation in outcomes, as expected, and to a similar degree as our systematic reviews on other prolapse interventions . Intraoperative and postoperative outcomes were the domains extensively documented.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This systematic review aimed to evaluate the selection and reporting of outcomes and the use of outcome measures in RCTs evaluating surgical treatments for posterior vaginal prolapse. We demonstrated a wide variation in outcomes, as expected, and to a similar degree as our systematic reviews on other prolapse interventions . Intraoperative and postoperative outcomes were the domains extensively documented.…”
Section: Discussionsupporting
confidence: 71%
“…The current findings are consistent with our recent systematic reviews of other pelvic floor disorders (perineal, anterior, mesh, apical). Inherent causes of these variations are expected to feature in all such trials and may be secondary to the lack of standardization of surgical techniques, surgical routes, different materials, and/or different specialties (gynecology, urogynecology, colorectal surgery) performing the surgical procedures for posterior compartment prolapse, in addition to inherent causes that may apply to all trials, such as research priorities, underreporting of adverse events, overreporting of success outcomes, and surgeon's preference or expertise in specific procedures.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the counselling of patients with pelvic organ prolapse and the fitting of pessaries by an advanced nurse practitioner is an effective conservative treatment [23,24]. Pessary treatment is gaining more importance as part of a urotherapy, especially since pelvic organ prolapse surgery is under debate due to recurrences and complication rates [25]. Pessaries are a safe and effective treatment option for women with pelvic organ prolapse; managing these patients needs person-centered care, which is a core activity of urotherapists [26].…”
mentioning
confidence: 99%
“…At short-term follow-up, the procedure was successful in 50 out of 51 women, with no objective evidence of uterine prolapse on examination [45]. High patient satisfaction with low rates of apical prolapse recurrence was found at mean follow-up of 2 years [46]. Furthermore, the risk of repeat apical surgery at one year after laparoscopic sacrohysteropexy was similar as compared to vaginal hysterectomy, suggesting this procedure is a safe surgical alternative to vaginal hysterectomy [47].…”
mentioning
confidence: 86%
“…outcomes and 66 outcome measures were identified [46]. As a result of heterogenous outcomes, meaningful meta-analysis of POP outcome data is impossible [47].…”
Section: Outcomes After Pop Treatmentmentioning
confidence: 99%